Economic Crisis and Pandemic Versus Business Operation - Jerzy WACHOL (Communications of International Proceedings, 2021)
The study presents the functioning of businesses during the pandemic and economic crisis, taking into particular consideration the macro environment, against the technological, economic and social transformations of the 21st century. The global socioeconomic data are presented and discussed. Unfortunately, it might be that the EU will weaken in the face of the pandemic, internal differences, economic and political problems, lack of development, ineptitude at management, lack of effective border protection, Brexit, conflicts, competition from China, lack of vaccine and poorly controlled migrations. The study presents selected elements of management and trends of changes in the organisation in the future. At present, businesses mostly value survival, marketing, finance, profit, strategies, human resources, innovativeness, modern management methods and organisational forms etc. Employees mostly cherish health, family, finance and survival. On the other hand, IT elements have already gained an important position, which is on the rise, particularly in the face of the pandemic, remote work and global crisis. Based on the collected statistical data, own studies, observations and literature, conclusions were drawn concerning the trends governing the transformations of organisations and the application of modern management concepts and business management forms in the global economy in times of the pandemic and economic crisis.
Keywords: Economic Crisis; Business Environment; Pandemic; Innovativeness